2011
DOI: 10.1371/journal.pone.0017890
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab Induces Clonal Expansion of γδ-T Cells in Crohn's Disease: A Predictor of Lymphoma Risk?

Abstract: BackgroundConcominant with the widespread use of combined immunotherapy in the management of Crohn's disease (CD), the incidence of hepato-splenic gamma-delta (γδ)-T cell lymphoma has increased sharply in CD patients. Malignant transformation of lymphocytes is believed to be a multistep process resulting in the selection of malignant γδ-T cell clones. We hypothesised that repeated infusion of anti-TNF-α agents may induce clonal selection and that concurrent treatment with immunomodulators further predisposes p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…Further investigation will now be required to identify the microbial/host-derived signals that may drive this process, although these are likely to include increased intestinal permeability (17), changes in the composition of the microbiota (1,44), and systemic priming of innate leukocytes by bacterial products translocated from the gut (21). Indeed, it has already been reported that environmental exposures influence γδ T cell frequency in human peripheral blood (25) and that stable expansions of Vδ2 T cells can occur in the circulation of patients with IBD (45,46). Consistent with these data, Vδ2 T cells have also been identified in the gut in a small number of CD patients (13,14), although the role played by these cells in mucosal inflammation in CD has, until now, remained obscure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further investigation will now be required to identify the microbial/host-derived signals that may drive this process, although these are likely to include increased intestinal permeability (17), changes in the composition of the microbiota (1,44), and systemic priming of innate leukocytes by bacterial products translocated from the gut (21). Indeed, it has already been reported that environmental exposures influence γδ T cell frequency in human peripheral blood (25) and that stable expansions of Vδ2 T cells can occur in the circulation of patients with IBD (45,46). Consistent with these data, Vδ2 T cells have also been identified in the gut in a small number of CD patients (13,14), although the role played by these cells in mucosal inflammation in CD has, until now, remained obscure.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, lymphoma risk in AZA-treated IBD has been reported to progressively increase with therapy duration (52), and older male patients are at the greatest risk of AZA-induced malignancy (53). Furthermore, HSTCL in AZA-treated CD is frequently of γδ T cell origin (49), and anti-TNF therapy reportedly increases the proliferation of γδ T cells in young, male CD patients (46). These data suggest that the Vδ2 T cell population itself may become dysregulated and eventually undergo malignant transformation in AZA-treated CD.…”
Section: Discussionmentioning
confidence: 99%
“…An example of this is seen in people with Crohn's disease who were found to have a global deficit in the number of cd T cells present. 98 Evidence that this may be a result of activation-induced cell death as opposed to an inherent immune anomaly of the disease comes from the observation that treatment with infliximab, an anti-TNFa agent, resulted in clonal expansion of cd T cells in Crohn's patients on treatment 105 , highlighting the potential in vivo role of TNFa signalling in cd T cell self-modulation. However, in vitro studies looking at the functional effects of infliximab on cd T cells derived from patients with Behçet's disease or rheumatoid arthritis, in contrast, found that the expansion and reactivity of these excitable T cells was notably impaired, 106,107 underscoring again the often discrepant outcomes when attempting to extrapolate findings from manipulated artificial settings in vitro to what occurs in vivo.…”
Section: Defined By Experiences Tainted By Innate Tendenciesmentioning
confidence: 99%
“…Because TNF-α is inhibitory to Vδ2+ T cell proliferation 10 , it is possible that IFX has promoted the proliferation of these cells. Further work is required to elucidate such a mechanism.…”
Section: Lettermentioning
confidence: 99%